A new species Spilarctia duda (Lepidoptera: Erebidae, Arctiinae) from China - Saldaitis, Aidas; Pekarsky, Oleg (Zootaxa, 2016)
A new tiger moth, Spilarctia duda sp. n., from southeast China, Sichuan is described. A diagnostic comparison with Spilarctia bipunctata Daniel, 1943 and Spilarctia clava (Wileman, 1910) is provided. During recent years the Chinese Arctiini have been intensively collected and explored (Fang, 2000; Dubatolov, 2010; Kishida, 2015; and numerous other publications), so the discovery of a distinctive new species near Maoxian, North part of Sichuan Province, was most unexpected.